Novel O-band tunable fiber laser using an array waveguide grating - Ahmad, Harith; Zulkifli, M.Z.; Latif, A.A.; Harun, Sulaiman Wadi (IOP Publishing, 2010)
A novel tunable fibre laser (TFL) operating in the ordinary band (O-band0 of 1310nm is proposed and demonstrated. The proposed TFL is developed using a 1x16 arrayed waveguide graitn (AWG) as a slicing mechanism for the broadband amplified spontaneous emission (ASH) source and an optical channel selector (OCS) to provide the tunability. A semiconductor optical amplifier (SOA) with a centre wavelength of 1310 nm serves as the compact gain medium for the TFL and also as a broadband ASE source. The TFL has a tuning range of 1301.26 nm to 1311.18 nm with 9.92 nm span and a channel spacing of 0.7nm. The measured output power is about -4 and .8dBm and with a side node suppression ratio (SMSR) of 29 to 33DB